Evaluation of Child Sexual Abuse Cases - Kırcı, Güven Seçkin; Özer, Erdal; Birincioğlu, İsmail and Aydoğdu, İlhan Halil and Askay, Mehmet and İmamoğlu, Mustafa (The Bulletin of Legal Medicine, 2021)
Introduction: Child abuse is defined as the child’s being harmed by an adult physically, physchogically or both with a deliberate and preventable reason. The purpose of our study is to reach the profile of our region in terms of child abuse through the features of the victims applying to the centre, to reveal the possible differences by comparing the literature and the properties of our region, to define the additional risk factors to the ones known by the literature. Material and Method: Our study has been carried out in Trabzon Child Protection And Monitoring Centre and the children applying during one and a half year, between January 2015 and June 2016, have been included. The study involves the retrospective evaluation of the records kept by the centre. Results: Considering the gender of 103 children we evaluated, it is seen that 86 (83,5%) of them are girls; 17 (16,5%) of them are boys and the girl/boy ratio is 0.19. Considering the age groups, 19 (18,4%) of them are 9 or younger; 37 (35,9%) of them are between 10 and 14; 47 (45,6 %) of them are 15 and older. While the youngest age identified in our study is 4, the oldest child age is 18. The average of age is 13.11±3.817. Discussion: In child abuse, the victim hides the abuse for years due to fear, threat or believing not to be relied on and be humiliated, therefore, victims who suffer from recurrent abuses for long years come out.